Seorang Pria Sehat Berusia 23 Tahun dengan Pingsan Setelah Bermain Futsal: Kasus Rhabdomyolysis yang disebabkan oleh aktivitas: Laporan Kasus - David Kristianus; Jonkie Budi Tirtadjaja (PT Kalbe Farma Tbk., 2025)
Introduction: Exertional rhabdomyolysis (ER) is a medical condition resulting from strenuous exercise characterized by skeletal muscle damage followed by the release of intracellular components into the circulation. ER has various clinical manifestations and is associated with various complications that increase morbidity and mortality. Case: A 23-year-old male came to the emergency department with decreased consciousness after playing futsal. After urinary catheter insertion, brown-colored urine was observed. Laboratory examination showed increased serum CK level (199,011 IU/L), increased serum creatinine, hyperkalemia, and metabolic acidosis. The diagnosis was exertional rhabdomyolysis, acute kidney injury, hyperkalemia, and metabolic acidosis. Conclusion: The condition of the patient improved after aggressive intravenous rehydration, intravenous insulin, and sodium bicarbonate therapy. Prompt diagnosis and appropriate management can reduce complications, morbidity and mortality.